Pengembangan Instrumen Asesmen Keterampilan Pemecahan Masalah Peserta Didik SMA Negeri 1 Kediri Pada Materi Ekosistem - Risma Ayu Nur Rahma Risma (Universitas Nusantara PGRI Kediri, 2021)
The skill to solve a problem is one of the skills that must be mastered by students in the 21st century. The problem of research is that there is no assessment that can measure the problem solving skills of students, especially in the material that is considered difficult by students, namely the ecosystem. Appropriate assessment is useful for developing students' problem solving skills. This study aims to develop a valid and reliable test instrument for students' problem solving skills. The research method used is a modified research and development (R & D) Plomp model. This research is limited to testing the feasibility of the developed instrument. The results of product development show that the average validity test by assessment expert lecturers is 93.75% in the valid category, material experts 89% in the valid category, linguists 81.25% in the valid category, practitioners by 84.5% in the valid category and 14 items were declared valid based on Pearson product moment calculations and had a reliability of 0.896 with a high reliability category. The conclusion of this study is that the problem-solving skills instrument developed by the indicators has met the requirements and is suitable for use as a learning evaluation tool for students at the high school level.